The World System of Pilgrimage Centres - Jackowski, Antoni; Ptaszycka-Jackowska, Danuta; Sołjan, Izabela (Turyzm/Tourism, 2002)
The discussion focuses on the notion of the world system of pilgrimage centres and the phenomenon of pilgrimage in the contemporary world. The authors emphasize the correlations among the centres, resulting from both their spatial and functional structure. The most significant pilgrimage centres in individual religions have been mentioned, with particular consideration of the Christian ones. Towards the end of the article, the main development trends in pilgrimage migrations and destinations have been outlined.